a平方b平方-c立方b平方-16a立方+16c立方
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 16:48:21
a平方b平方-c立方b平方-16a立方+16c立方a平方b平方-c立方b平方-16a立方+16c立方a平方b平方-c立方b平方-16a立方+16c立方a²b²-c²b&s
a平方b平方-c立方b平方-16a立方+16c立方
a平方b平方-c立方b平方-16a立方+16c立方
a平方b平方-c立方b平方-16a立方+16c立方
a²b²-c²b²-16a³+16c³
=b²(a²-c²)-16(a³-c³)
=b²(a+c)(a-c)-16(a-c)(a²+ac+c²)
=(a-c)[b²(a+c)-16(a²+ac+c²)]
a平方b平方-c立方b平方-16a立方+16c立方
a立方+b立方=?a立方-b立方=?(a+b+c)平方=?
a立方+a平方b-a平方c-abc
(a平方b立方)立方=()?
因式分解:a立方+a平方b-ab平方-b立方
8a立方b平方-12ab平立方c
a平方b`(ab立方)平方
{-c平方分之2a平方b}立方 化简
12a平方b立方+6a平方b平方-18a立方b平方
a,b,c为正整数,求证a八次+b八次+c八次≥a立方b立方c平方+a平方b立方c立方+a立方b平方c立方
已知b平方=ac,求(a立方+b立方+c立方)分之(a平方*b平方*c平方)*(a立方分之1+b立方分之1+c立方分之1)的值
已知a+b+c=1,a平方+b平方+c平方=2,a立方+b立方+c立方=3,求a,b,
因式分解:a平方b—b立方
(-a平方b立方)*(-3a)
已知a+b+c=0 求证a立方+a平方c+b平方c-abc+b立方=0
(-a平方b/c)立方×(-c平方/ab)平方÷(bc/a)四次方
x+y+z=a…x平方+y平方+z平方=b平方…x立方+y立方+z立方=c立方…求xyz
(-3a/4b平方)立方/6a平方b